Cytological Pattern of Papanicolaou Smears in a Tertiary Care Centre of Bihar, India - Srivastava, Naresh Kumar (Asian Journal of Medical Research, 2019)
Background: Cervical cancer is the most common although preventable cancer of Indian females. It does not develop suddenly from normal epithelium but is presented by a spectrum of intraepithelial neoplasia. Pap smear is an ideal screening method and low cost effective test to detect intraepithelial neoplasia especially in developing countries although it has limitations and needs confirmation by histopathology. The objective of this study was to assess the prevalence and pattern of cervical lesions using conventional Pap smear method. Subjects and Methods: It was a retrospective study conducted in a tertiary care institute of Rohtas, Bihar. The data of two years was collected from medical records department. Results: Out of 664 smears, 397 (59.79%) were abnormal Pap smears, 169 (25.45%) were normal Pap smears while 98 (14.76 %%) smears had inadequate sample material to be examined. Out of 397 abnormal smears, 362 (91.18%) smears reported to have inflammatory/reactive changes whereas 10 (2.51%) had atrophic changes in Pap smear and abnormality in epithelial cell was reported in 25 (6.29%) smears. Conclusion: Pap smear is an effective screening procedure to detect cervical cytological abnormalities. Routine cytological screening by Pap smear should be offered to all women above 19 years or within 3 years of sexual activity. There is an urgent need to improve the awareness about the disease among females and skills of health care workers should be honed for preparation of Pap smears.